Cu–Cr–Mo alloys prepared by mechanical alloying and hot isostatic pressing - WANG Silun; CUI Zizhen; LIU Quanyi; XIE Fei; LIN Yansong (Fenmo yejin jishu)
The Cu–9.3Cr–9.3Mo (mass fraction) powders were prepared by mechanical mixing and mechanical alloying, respectively, and the Cu–Cr–Mo alloys were pressed by hot isostatic pressing. The phase composition, organizational structure, and particle size of the powders were characterized by X-ray diffraction and laser particle size analysis. The relative density, hardness, conductivity, and microstructure of the alloys were measured. The results show that, the mechanical alloying process can induce the formation of Cu–Cr–Mo supersaturated solid solution, improve the degree of lattice distortion, and reduce the grain size and powder particle size. The prepared alloy blocks by mechanical alloying have the high hardness, ideal relative density, and electrical conductivity, showing the excellent comprehensive properties.